Pemberdayaan Siswa Sekolah Dasar dalam Pelatihan dan Edukasi Perawat Cilik untuk Pencapaian Desa Peduli Kesehatan - Idelriani I; Hadijah H; Robertus Masyhuri (PT.Mantaya Idea Batara, 2022)
Community service activities carried out in Sapanang village, Kec. Binamu, Kab. Jeneponto on Saturday, March 20, 2021, 09.00-13.00 WITA is a community service activity by empowering elementary students in training and educating little nurses in the context of achieving health care villages. The purpose of this activity is to provide an introduction to little nurses to elementary school students and provide training skills in the form of little nurse education to elementary school students so that people will understand better and know the right first treatment that can be done if there are health problems. The community will also be more familiar with the nursing profession in daily life so that the community will be able to create a healthcare village. From the 25 children who participated in the little nurses training and education activities, the results were quite satisfied with the children who were given education regarding little nurses' understanding of what the role of a nurse was. Some of the obstacles in the implementation of training and education for little nurse training include (1) there are limitations in supporting facilities, including limited tools and health workers in demonstrating the duties and functions of little nurses in caring for patients so that the activity lasts quite a long time. (2) the little nurse demonstration activity which was planned to run for 1 day could not be realized optimally due to the limited distribution of time for school entry considering that it was still in pandemic condition so the number of participants was limited.